2021
DOI: 10.3389/fpsyg.2021.654825
|View full text |Cite
|
Sign up to set email alerts
|

Associations Among the Big Five Personality Traits, Maladaptive Cognitions, and Internet Addiction Across Three Time Measurements in 3 Months During the COVID-19 Pandemic

Abstract: The present study examined the longitudinal association among the Big Five personality traits, maladaptive cognitions, and Internet addiction during the COVID-19 pandemic. A total of 481 Chinese university students (247 men; mean age = 20.31 years) were surveyed three times (interval of 1 month) by using the Chinese version of the Big Five Personality Traits Scale, Maladaptive Cognitions Scale, and Internet Addiction Scale. The results of a cross-lagged panel analysis highlighted that (i) extraversion, agreeab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
2
12
1
Order By: Relevance
“…On the other hand, extroverted individuals are, at the same time, often impulsive and tend to search for new stimulation, which makes them more prone to engage in addictive behavior [ 18 ]. However, contrary to our results, some studies found that extraversion was negatively associated with IA [ 15 , 16 , 61 , 62 , 63 , 67 , 68 , 69 ]. Considering the openness to new experiences, our study revealed that there is a positive association between higher openness to new experiences and IA, which had also been shown in other similar studies [ 16 , 18 , 69 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…On the other hand, extroverted individuals are, at the same time, often impulsive and tend to search for new stimulation, which makes them more prone to engage in addictive behavior [ 18 ]. However, contrary to our results, some studies found that extraversion was negatively associated with IA [ 15 , 16 , 61 , 62 , 63 , 67 , 68 , 69 ]. Considering the openness to new experiences, our study revealed that there is a positive association between higher openness to new experiences and IA, which had also been shown in other similar studies [ 16 , 18 , 69 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The present study confirmed that personality traits had a meaningful association with IA, which was also found in several other studies [ 10 , 15 , 18 , 59 , 60 , 61 ] and further revealed that Croatian university students’ higher neuroticism, higher extraversion, and higher openness to new experiences were significantly connected with IA. This finding is in concordance with the results of other similar studies that showed how higher neuroticism is positively related to IA, meaning that neuroticism can be a risk factor for IA development [ 6 , 14 , 15 , 18 , 26 , 55 , 61 , 62 , 63 , 64 ]. The explanation for the observed connection lies in the fact that individuals with higher neuroticism experience more troubled relationships and distressed situations, and because of that, they are more prone to use the Internet to avoid the aforementioned unpleasant experiences [ 18 ].…”
Section: Discussionsupporting
confidence: 91%
“…Numerous intrapersonal and interpersonal risk factors have been identified as influencing an individual's level of vulnerability, exposure, or response to a causative agent (Internet feature). 41,42 Individual intrapersonal and interpersonal variables, such as personality traits and psychosocial well-being have received the most attention in the existing literature on IA among adolencents. 16,43,44 a.…”
Section: Individual Factors (Host)mentioning
confidence: 99%
“…For this research, the most used psychometric instrument is the Big-Five (Goldberg, 1992). [8] The study of Tian Yu et al 2021, [9] examined the longitudinal association among the Big-Five personality traits, maladaptive cognitions, and internet addiction during the COVID-19 pandemic in a sample of Chinese students. The results of the analysed data showed that (a) extraversion, agreeableness, conscientiousness, and openness were negatively associated with maladaptive cognitions and internet addiction, whereas neuroticism was found to be positively associated with maladaptive cognitions and internet addiction The study of Zhang Yue et al, 2021 [10] highlights that impulsivity, social support, and depression may predict internet addiction among male college freshmen.…”
Section: Psychological Characteristicsmentioning
confidence: 99%